Clinico-epidemiological study of donovanosis in Durban, South Africa. Issue 2 (April 1993) - O'Farrell, N
Abstract : OBJECTIVE: To describe the epidemiological and clinical features of donovanosis and their relevance to the possible coincident risk of HIV-1 transmission in patients attending an STD clinic. DESIGN: Assessment of patients with donovanosis diagnosed by the detection of Donovan bodies on tissue smears stained by the RapiDiff technique. SETTING: City Health STD Clinic, King Edward VIII Hospital, Durban, South Africa. PARTICIPANTS: One hundred and seventy one patients with donovanosis. RESULTS: Donovan bodies were detected in 171 (130 men, 41 women). Ulcers were present for longer than 28 days in 72 (55.4%) men and 19 (46.3%) women. Ninety five (55.6%) came from rural areas. Lesions were ulcero-granulomatous in 162, hypertrophic in eight and necrotic in one. Anal lesions were detected in one woman. Only one of 21 regular sexual partners examined was infected with donovanosis. Complete healing was observed in 41 (24%) who attended for follow up. Extensive lesions were sometimes observed in pregnant women. Serological tests for syphilis were positive in 40 (23.4%). HIV-1 antibodies were detected in 4/48 men and 0/15 women who underwent HIV testing. Donovanosis ulcers in three HIV-1 seropositive men were cured by standard antibiotic therapy. CONCLUSIONS: Delay in presentation, extensive areas of genital ulceration and lack of co-existent infection with donovanosis among sexual partners were notable features. Primary health care facilities in rural areas do not appear to be providing an adequate service for patients with donovanosis. HIV control programmes should consider specific measures aimed at eradicating donovanosis in areas where the condition is prevalent.